Therapeutic Effect of Autologous Activated Platelet-rich Plasma Therapy on Mid-dermal to Full-thickness Burns: A Case Series - Karina, Karina; Ekaputri, Krista; Biben, Johannes Albert; Hadi, Pritha; Andrew, Hubert; Sadikin, Patricia Marcellina (Archives of Plastic Surgery, 2022)
Although modern medicine has made great strides in the management of burn injuries, associated complications such as pain, infection, dyspigmentation, and scarring have yet to be fully dealt with. Although skin grafting and meshing are routinely performed on burn patients, this method poses a risk for adverse effects. Activated autologous platelet-rich plasma (aaPRP), which is increasingly used in the field of plastic surgery, contains growth factors beneficial for wound regeneration. Seven cases of burns with varying severity and conditions that were treated with intralesional subcutaneous injection and intravenous aaPRP are presented and discussed herein. This case series indicates that subcutaneous and intravenous aaPRP is a safe procedure with the potential to be an alternative when skin grafting cannot be done or as an adjunct treatment to skin grafting.
Keywords: platelet-rich plasma; burns; skin transplantation